1998
DOI: 10.1074/jbc.273.38.24420
|View full text |Cite
|
Sign up to set email alerts
|

Kringle 2 Mediates High Affinity Binding of Plasminogen to an Internal Sequence in Streptococcal Surface Protein PAM

Abstract: Many cells express receptors for plasminogen (Pg), although the responsible molecules in most cases are poorly defined. In contrast, the group A streptococcal surface protein PAM contains a domain with two 13-amino acid residue long repeated sequences (a1 and a2) responsible for Pg binding. Here we identify the region in Pg that interacts with PAM. A radiolabeled proteolytic plasminogen fragment containing the first three kringles (K1-K3) interacted with streptococci expressing PAM or a chimeric surface protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 37 publications
4
68
0
Order By: Relevance
“…Thus, binding interactions of VEK-peptides, regardless of their oligomerization states, mediate the transformation of the tight (T) to the relaxed (R) conformations of hPg. Although binding of these peptides are specific for the LBS of K2 hPg (14,38), this does not rule out the possibility that exosites, especially in the longer peptides, interact with other FIGURE 1. Sedimentation equilibrium ultracentrifugation analysis of VEK-peptides.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, binding interactions of VEK-peptides, regardless of their oligomerization states, mediate the transformation of the tight (T) to the relaxed (R) conformations of hPg. Although binding of these peptides are specific for the LBS of K2 hPg (14,38), this does not rule out the possibility that exosites, especially in the longer peptides, interact with other FIGURE 1. Sedimentation equilibrium ultracentrifugation analysis of VEK-peptides.…”
Section: Resultsmentioning
confidence: 95%
“…It has been demonstrated that PAM binding to K2 hPg is mediated by an internal a1a2 repeat domain in the N terminus of PAM (14,42). The importance of the a1a2 domain of PAM in hPg binding has also been demonstrated in Arp4, an M-like protein, which does not interact with hPg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lpd attaches plasminogen via a major binding site localized in kringle domain 4. Streptococcal surface protein PAM binds human plasminogen via kringle domain 2, and the Streptococcus canis protein SCM binds plasminogen via kringle domain 5 (53,54). Thus, the three bacterial proteins bind to different kringle domains of plasminogen.…”
Section: Discussionmentioning
confidence: 99%
“…Plasminogen binding M proteins have been well characterised in vitro (12,(14)(15)(16)(17)(18)(19)(20), however the direct contribution of these proteins to GAS virulence has not been defined. Whilst the deletion of the PAM gene results in a loss of virulence (7,14), this may be due to a loss of other functions such as protection from phagocytosis or binding of other host molecules attributed to M proteins (21).…”
Section: Introductionmentioning
confidence: 99%